On the Relation between Translations and the Reception of the Children’s and Household Tales (Kinder- und Hausmärchen) by Brothers Grimm in Poland - Eliza Pieciul-Karmińska (Literatura Ludowa. Journal of Folklore and Popular Culture, 2023)
The fairy tales by the Brothers Grimm are the most often translated work of German literature. All over the world these tales are read in translations that are not identical to the original. In Poland, these important texts are also read in various versions translated into Polish, which raises a question of how the form and content of different translations and adaptations may influence the reception of these German tales. Referring to important studies by folklorists Helena Kapełuś and Dorota Simonides, the author of the article indicates which research topics should be continued and deepened in the field of the Grimm research in Poland.